Potency Analysis of Semi-Synthetic Cannabinoids in Vaping Oils Using Liquid Chromatography Diode Array Detector with Electrospray Ionization Time-of-Flight Mass Spectrometry for Confirmation of Analyte Identity - Shaozhong Zhang; Md Mahmud Alam; Brent D. Chandler; Jocelyn P. Lanorio; Caitlin Deskins; Liguo Song (Molecules, 2025)
Since the 2018 Farm Bill legalized hemp, semi-synthetic cannabinoids, typically derived from hemp-extracted CBD, have been marketed as offering a “legal high”, raising concerns about consumer safety, labeling, and regulation. Consequently, the potency analysis of these compounds has become increasingly important. To address this need, an LC-DAD method was developed for the quantification of seventeen cannabinoids, selected based on the synthetic pathways of semi-synthetic cannabinoids. These included naturally occurring compounds, semi-synthetic derivatives, and byproducts (CBC, CBD, CBDV, CBG, CBN, CBN-O-acetate, CBT, 9(R)-HHC, 9(S)-HHC, 9(R)-HHC-O-acetate, 9(S)-HHC-O-acetate, Δ8-THC, Δ9-THC, Δ9,11-THC, Δ8-THC-O-acetate, Δ9-THC-O-acetate, and Δ9-THCV), using abnormal CBD as an internal standard. The method was validated according to ISO 17025 guidelines, demonstrating a linear calibration range from 0.1 to 50 µg/mL. The method was further applied to the potency analysis of one Δ8-THC, two THC-O-acetate, two HHC, and one HHC-O-acetate vaping oil sample. Using an innovative method to recover the contents of vaping cartridges, cannabinoids were extracted using methanol, diluted to a concentration of 50 µg/mL, and analyzed using the validated LC-DAD method, which provided a quantifiable range of 0.1 to 100% (w/w). Method specificity was evaluated using ESI/TOFMS and showed minimal interference, despite the presence of other isomers of the semi-synthetic cannabinoids in the samples.